EVALUASI PENILAIAN KINERJA DOSEN DIDASARKAN PADA KOMPETENSI (STUDI KASUS PADA DOSEN FEB UNIVERSITAS DHARMA ANDALAS PADANG) - Prima Yulianti (Menara Ilmu, 2020)
Abstract :This study aims to determine the effect of pedagogical competence, personality competence, social competence and professional competence on the performance evaluation of Lecturers at the University of Dharma Andalas. This study uses independent variables (X) namely Pedagogical Competencies (X1), Personality Competencies (X2), Social Competencies (X3), and Professional Competencies (X4), and the dependent variable (Y) namely Teacher Performance Assessment (Y). The population is all students of the Faculty of Economics and Business, Dharma Andalas University. The sampling technique was random sampling with a total sample of 462 respondents. The data analysis method used is multiple linear regression analysis. The results obtained from this study indicate that both parsia and simultaneous variables of pedagogical competence, personality competence, social competence and professional competence have a positive and significant impact on Lecturer Performance Assessment. Keywords: Pedagogic Competence, Personality Competence, Social Competence, Professional Competence, Lecturer Performance Assessment